Clinical effectiveness and safety of antazoline‐based therapy in patients with stable coronary artery disease undergoing pharmacological cardioversion of short‐duration atrial fibrillation in the emergency department. Issue 6 (20th October 2018) - Farkowski, Michal M.; Maciag, Aleksander; Zurawska, Malgorzata; Kowalik, Ilona; Szwed, Hanna; Pytkowski, Mariusz
Summary: Introduction: Options for a pharmacological cardioversion (CV) of short‐duration atrial fibrillation (AF) in patients with a stable coronary artery disease (CAD) are limited to amiodarone or vernakalant. Antazoline has been reported to achieve high rates of AF conversion to sinus rhythm, but data on its effectiveness and, more importantly, safety in stable CAD patients, have been sparse. Aims: To assess the effectiveness and safety of antazoline‐based therapy in patients with a stable CAD undergoing pharmacological CV of short‐duration AF in the emergency department (ED). Results: A retrospective case‐control study. We conducted an analysis of medical records of patients with a stable CAD undergoing CV of short duration (≤48 hours) AF in the ED using intravenous antazoline. The main endpoints of the study were successful cardioversion of AF and hospitalization due to the adverse effects (AE) of the treatment. Between 2008 and 2012, out of 548 CVs, antazoline was administered 334 times: 138 in CAD and 196 in the control group. Patients in the CAD group were older and had more comorbidities than controls; 65 patients had had a history of myocardial infarction (MI). In CAD group, the effectiveness was higher (82.6% vs 63.8%, RB: 1.30 [95% CI: 1.14‐1.48], P  = 0.0002) and the hospitalization rate due to AE was similar (1.4% vs 4.1%, RR: 0.36 [95% CI: 0.08‐1.65], P  = 0.2054) to the control group. Among patients with CAD, a history of MI did not influence the effectiveness or safety of the CV ( P  = 0.2252 and P  = 1.0000, respectively). Conclusions: In selected patients with a stable CAD, even with a history of MI, antazoline‐based CV of short‐duration AF may be an effective and safe therapeutic option.